2021
DOI: 10.3390/ijms22094483
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Oxidative Stress, Inflammation and Angiogenesis in Bladder Cancer Development

Abstract: In 2018, 550,000 people were diagnosed with bladder cancer (BC), of which nearly 200,000 people died. Moreover, men are 4 times more likely than women to be diagnosed with BC. The risk factors include exposure to environmental and occupational chemicals, especially tobacco smoke, benzidine and genetic factors. Despite numerous studies, the molecular basis of BC development remains unclear. A growing body of evidence suggests that inflammation, oxidant-antioxidant imbalance and angiogenesis disorders may play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 297 publications
(407 reference statements)
2
44
0
Order By: Relevance
“…Bladder cancer has become one of the most common cancers worldwide. More than 2 million woman were diagnosed patients were diagnosed, and more than 0.6 million death in 2018 ( Wigner et al, 2021 ). LncRNAs have been identified as novel essential regulators of various human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer has become one of the most common cancers worldwide. More than 2 million woman were diagnosed patients were diagnosed, and more than 0.6 million death in 2018 ( Wigner et al, 2021 ). LncRNAs have been identified as novel essential regulators of various human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies confirm that the excessive ROS production contributes to the progression of carcinogenesis and neoplasms [ 38 , 39 ]. In the case of cancer dynamics, it has been shown that it is directly related to the hyperproduction of lipid peroxidation products, as well as DNA-structurally diverse compounds, which can be found in body fluids.…”
Section: Role Of Oxidative Stress In Cancer Progressionmentioning
confidence: 99%
“…In the case of cancer dynamics, it has been shown that it is directly related to the hyperproduction of lipid peroxidation products, as well as DNA-structurally diverse compounds, which can be found in body fluids. The most common markers for the determination of pathology are malondialdehyde (MDA) and 8-hydroxy-2′-deoxyguanosine (8-OHdG), found in the blood of patients, and 8-isoprostaglandin F2α (8-iso-PGF2α), found in urine and blood ( Figure 3 ) [ 38 , 40 , 41 ].…”
Section: Role Of Oxidative Stress In Cancer Progressionmentioning
confidence: 99%
“…Thus, it was long considered antioxidants to be defensive weapons that can help prevent and suppress the development of cancerous processes, but lately a body of scientific evidence is emerging to challenge the efficacy or even the safety of these complementary alternative treatments calling for a reconsideration of a new paradoxical concept of double-edged antioxidants [ 14 ]. The topic on where the beneficial effects of the antioxidants become actually nocive in cancer therapy has been discussed in some relevant and recent reviews [ 15 ], or articles concerning (only) certain specific areas, such as bladder cancer development [ 16 ], or ROS- (reactive oxygen species-) based nanomaterials [ 17 ], but the exact role of antioxidants and the ambiguity of the oxidants-antioxidants interplay remain unclear. The current study is aimed at offering a comprehensive picture of oxidative stress implication in the various cancer developments and subsequently summarizing the most relevant findings of the anticancer role of all classes of antioxidants, presented here according to their conventional classification.…”
Section: Introductionmentioning
confidence: 99%